TEACHING PERFORMANCE IN CARING FOR STUDENTS WITH AUTISM SPECTRUM DISORDER - ASD IN A MULTIFUNCTIONAL CLASSROOM: A QUALITATIVE STUDY AT MARIA RAIMUNDA MOTA DE ANDRADE STATE SCHOOL - de Souza Cazaes, Gilson (Revista Gênero e Interdisciplinaridade, 2025)
This article aims to investigate the role of teachers at Escola Estadual Maria Raimunda Mota de Andrade in supporting students with Autism Spectrum Disorder (ASD) in the Multifunctional Classroom. The qualitative research was conducted through semi- structured interviews with teachers who work with ASD students, aiming to understand their pedagogical strategies, the daily challenges they face, and their perceptions of these students’ development. Data analysis identified key inclusion practices, structural and formative barriers, as well as progress and support needs within the school context. The results highlight the importance of strengthening teachers’ continuous training and providing more efficient support, both in terms of pedagogical resources and collaboration between school and family, to ensure a more effective and inclusive approach for students with ASD. This study aims to contribute to the ongoing discussion about inclusive education and the essential role of Multifunctional Classrooms in developing pedagogical practices that promote learning and socialization for students with special educational needs.